2021
DOI: 10.1002/app.50889
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐contact hybrid thermal conductive filler Al2O3@AgNPs optimized three‐dimensional thermal network for flexible thermal interface materials

Abstract: In this work, a multi‐contact Al2O3@AgNPs hybrid thermal conductive filler was synthesized by in‐situ growth method to fill high thermal conductivity polydimethylsiloxane (PDMS)‐based composites to prepare TIMs. And the thermal conductivity, electrical conductivity, and mechanical properties of the composite materials were studied. During the synthesis process of the multi‐contact hybrid filler, different concentrations of silver ions were reduced to generate silver nanoparticles and attached to the surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It can thus be suggested that compared to other morphologies, such as particles, microspheres, and foams, the yolk–shell structure assembled from nanosheets has a decided advantage in thermally conductive fillers. 18,20,37–50…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can thus be suggested that compared to other morphologies, such as particles, microspheres, and foams, the yolk–shell structure assembled from nanosheets has a decided advantage in thermally conductive fillers. 18,20,37–50…”
Section: Resultsmentioning
confidence: 99%
“…It can thus be suggested that compared to other morphologies, such as particles, microspheres, and foams, the yolk-shell structure assembled from nanosheets has a decided advantage in thermally conductive fillers. 18,20,[37][38][39][40][41][42][43][44][45][46][47][48][49][50] By contrast, g-Al 2 O 3 @C YSMSs have a slightly lower HC of 2.06 W m À1 K À1 (2.4% decrease), which is mainly caused by the phonon scattering at the interface between g-Al 2 O 3 and amorphous carbon, together with the intrinsic low heat/electrical conductance of amorphous carbon with low graphitization (Fig. 7c1).…”
Section: The Thermal Performancementioning
confidence: 99%
“…Therefore, it is necessary to select the appropriate reagent, dose, and method to modify the thermally conductive filler. Huang et al 135 synthesized a multi‐contact Al 2 O 3 @AgNPs hybrid thermal conductive filler by in‐situ growth method. Silver nanoparticles with different concentrations of silver ions were reduced to form and attached to the Al 2 O 3 surface.…”
Section: Composition Of Thermal Conducting Polymermentioning
confidence: 99%
“…7a3). 2,[29][30][31]42,[49][50][51][52][53][54][55][56][57][58][59][60][61][62] Fig. 7b1-b3 illustrate the thermal conduction mechanism of Fe-doped CeO 2 /Ce(OH) 3 CSNFs.…”
Section: Heat Properties and Mechanismmentioning
confidence: 99%